Colluding Against Environmental Regulation - Alé-Chilet, Jorge; Chen, Cuicui; Li, Jing; Reynaert, Mathias (Review of Economic Studies, 2026)
Abstract We study collusion among firms against imperfectly monitored environmental regulation. Firms increase variable profits by violating regulation and reduce expected noncompliance penalties by violating jointly. We consider a case of three German automakers colluding to reduce the effectiveness of emissions control technology. By estimating a structural model of the European automobile industry from 2007 to 2018, we find that collusion lowers expected noncompliance penalties substantially and increases buyer and producer surplus. Due to increased pollution, welfare decreases by € 1.57–5.57 billion. We show how environmental policy design and antitrust play complementary roles in preventing noncompliance.